1883 Wis. Sess. Laws 713, ch. 6, § 3, pt. 56 - (:unkn) unknown (General Publisher, 1883)
Prohibited the carrying of a concealed pistol or colt, or slungshot, or cross knuckles or knuckles of lead, brass or other metal or Bowie knife, dirk knife, or dirk or dagger, or any other dangerous or deadly weapon. Punishable by confiscation of the weapon.
--
Keywords: CARRY - CONCEALED